SERIAL KILLER IN POPULAR LITERATURE: A FORMULA ANALYSIS OF HANNIBAL LECTER SERIES - Dian Nur Endah (Universitas Gadjah Mada, 2016)
Using textual analysis, this research attempts to find out the formula of Hannibal Lecter novels. These formula is analyzed and studied to acquire convention and invention in Hannibal Lecter characterization compared to other serial killer fictions. These two aspects are the foremost things that enable Hannibal Lecter novel series become acceptable and popular in American society. The result of this research is that there are some aspects in Hannibal Lecter characterization that are defined as convention of serial killer genre; 1) depiction of serial killer as white male, 2) depiction of serial killer as being highly intelligent and strong. Meanwhile, aspects that show invention of serial killer characerization are; 1) Depiction of serial killer as person who commits killing to bad people, 2) Performing cannibalism practice as civilized action, 3) Being woman lover, not misogynist, and 4) Being sociable man.Keywords: serial killer, formula, convention, invention, crimes